Primary Surgical Treatment in Very Advanced (T4b) Oral Cavity Squamous Cell Carcinomas. (5th January 2021) - Patel, Evan J.; Oliver, Jamie R.; Vaezi, Alec; Li, Zujun; Persky, Michael; Tam, Moses; Hu, Kenneth S.; Jacobson, Adam S.; Givi, Babak
Abstract : Objectives: To describe patterns of primary surgical treatments in patients with T4b oral cavity squamous cell carcinoma (OCSCC). Study Design: Historical cohort study. Setting: National Cancer Database. Methods: Review of the National Cancer Database between 2004 and 2017 for all T4b OCSCCs. Only patients with curative treatment methods were included in the survival analysis. Surgical and nonsurgical outcomes were compared by multivariable and propensity score matching analysis. Results: A total of 1515 cases of T4b OCSCC were identified. A minority of patients (n = 363, 24.0%) underwent curative treatment; among these, 206 (56.7%) underwent primary surgery. Median length of follow‐up was 24 months. The 90‐day mortality of patients who underwent surgical treatment was 1.0%. The 2‐year survival was higher for patients who underwent surgery + chemoradiotherapy (CRT) as compared with CRT (64.6% vs 45.2%, P <. 001). On multivariable analysis, surgery + CRT was associated with longer survival. In a propensity score–matched cohort of 312 patients, 2‐year survival remained higher in the surgical group versus the nonsurgical group (59.4% vs 45.5%, P =. 02). Among patients who underwent surgery + CRT, there was no difference in 2‐year survival between clinical T4a and T4b (59% vs 64.6%, P =. 20). Conclusions: A minority of patients with T4b OCSCC undergo treatments with curative intent. A subset of patients underwent primary surgical treatment, which was associated with longer survival. The T4b classification might entail a heterogenous group, and further studies in revision of this classification might be justified.